A ALCOA NO MARANHÃO E O DESENVOLVIMENTO SOCIOECONÔMICO REGIONAL - Costa, Silvia Cristina Mineu (2003)
The relation between Alcoa and the regional socioeconomic in Maranhão. We critically analysis the action of a multinational company at a peripheral area. We emphasize the external and internal factors in a capitalist globalization context of Brazilian economy, due to foreign investment in Brazil, specific in Maranhão. We also analysis the public powers participation in Alcoa s implantation process in São Luis and its consequences on Maranhense economy. Finally, we analysis Alcoa s action in Maranhão based on its own socioeconomic indicators.